A pyrene-based optical probe capable of molecular computation using chemical input strings12. Issue 64 (12th July 2015) - Chhatwal, Megha; Kumar, Anup; Gupta, Rinkoo D.; Awasthi, Satish K.
<x xml:space="preserve">Abstract</x> Elucidation of molecular computing by employing a pyrene-based chemosensor with Cu2+, Fe3+, CN− and H+ ions as input stimuli and subsequent quantum yields as output responses.